CONSTRAINTS ON UPPER INNER-CORE STRUCTURE FROM WAVEFORM INVERSION OF CORE PHASES - Garcia R. (My University, 2002)
The determination of the inner-core boundary structure is key to understanding the mechanisms of inner-core growth, iron solidification and anisotropy formation in the inner core. A waveform inversion of a worldwide data set of PKIKP and PKiKP core phases is performed to investigate the velocity and the attenuation structure of this region. The data set is chosen to sample the top 50 km of the inner core. Two inversion methods combining time and frequency domain observations are presented. Synthetic tests are performed in order to evaluate the resolution and the confidence intervals of the model parameters. The attenuation of P waves in the uppermost inner core is poorly resolved but appears to be high $(Q < 100)$. The uppermost inner-core interface is divided into two regions: a region extending from 180°W to 60°E and characterized by negative P -wave velocity perturbations ($dV /V < 0 per cent)$, and a region extending from 60°E to 180°E and characterized by positive P -wave velocity perturbations $(dV /V ~ 1 per cent)$. The results of the inversion do not favour the presence of transverse isotropy aligned along the spin axis of the Earth in the uppermost inner core for these two regions. However, these regions are correlated with those where large-scale variations of the inner-core anisotropy have been determined previously in the deeper inner core, 100 km beneath the inner-core boundary.
Keywords: ATTENUATION; BODY WAVES; INNER CORE; INVERSION; P WAVES; WAVEFORM ANALYSIS